Utilization of Lignin from Oil Palm Empty Fruit Bunches (OPEFB) for the Fabrication of Eco-Friendly Superhydrophobic Sponges - Meiyanti Ratna Kumalasari; Yuni Damayanti Nainggolan; Jesika Nababan; Anastasya Isaura; Wenika Simbolon; Hana Esrani Togatorop; Rizki Rachmad Saputra; Siti Unvaresi Misonia Beladona; Ozi Adi Saputra (Indonesian Journal of Chemical Research, 2026)
The escalation of crude oil exploitation poses significant risks of leakage and oil spills in the oceans. Therefore, this research aims to synthesize superhydrophobic sponges utilizing lignin derived from Oil Palm Empty Fruit Bunch (OPEFB) waste. Lignin was isolated from OPEFB with the addition of 15% NaOH, followed by neutralization and purification using H₂SO₄, which yielded a recovery of 30.3%. Subsequently, melamine sponges were modified via a facile dip-coating technique using a mixture of lignin, Polydimethylsiloxane (PDMS), and (3-aminopropyl)triethoxysilane (APTES). The physicochemical properties and material performance were characterized using 1H-NMR, FTIR, and Water Contact Angle (WCA) measurements. 1H-NMR analysis confirmed the successful isolation of the lignin structure, while FTIR spectra verified the effective deposition of the silane-lignin layer on the sponge skeleton. Contact angle analysis results indicated a significant surface transformation, where the sponge shifted from a superhydrophilic nature 0° to a highly superhydrophobic state (170.91°). With such performance, this material holds great potential as an effective, eco-friendly adsorbent for oil spill remediation in aquatic environments.